PENGARUH MARKETING MIX PADA MINAT BELI GENERASI Z ATAS PRODUK MALANG STRUDEL - Irma Yunita; Fakhruddin Kurnia M (PIRSAP (Paser Institute for Scientific Research and Publications), 2025)
Indonesian culinary industry is getting more competitive with the emergence of innovative local culinary products in each region. One of the brands trying to adapt their marketing strategy to their target markets is Malang Strudel. This study aims to analyze the effect of the 4P (Product, Price, Place, and Promotion) marketing Mix on Generation Z's (Gen Z) purchase intention of Malang Strudel products. With Gen Z being known for their interest in digital and innovative marketing strategy, this research examines how far the 4P influences their purchase intention using a quantitative approach by spreading a questionnaire to 84 respondents living in Malang, Indonesia. The data was analyzed using SPSS to test the correlation between each variable. The results prove that the 4P marketing mix significantly influenced Gen Z’s purchase intention. The findings provide practical implications for business owners to plan effective marketing strategies for the Gen Z segment.